Characteristics of anti-Vibrio harveyi compounds produced by Bacillus spp. isolated from shrimp ponds (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rusmana I, Isramilda, Akhdiya A. 2021. Characteristics of anti-Vibrio harveyi compounds produced by Bacillus spp. isolated from shrimp ponds. Biodiversitas 22: 4872-4879. Pathogenic Vibrio spp. such as Vibrio vulnificus, V. alginolyticus, V. fluvialis, V. anguillarum, and V. harveyi caused shrimp diseases. The application of bacterial probiotics can control the growth of pathogenic Vibrio in shrimp. Bacillus spp. can produce antimicrobial compounds that inhibit the growth of pathogenic Vibrio spp. Isolation of Bacillus from several pond water samples, pond sediment, and shrimp intestines was successfully collected 175 isolates of Bacillus spp. Three isolates, i.e., Ltw54, Lts36, dan Lts40 had a high inhibitory index and stability in inhibiting the growth of Vibrio harveyi. Verification assay showed that Bacillus sp. Lts40 had the highest antimicrobial activity. The competition assay showed that Bacillus sp Lts40 isolates inhibited the growth of V. harveyi up to 81,8%. The antimicrobial compound produced by Bacillus sp. Lts40 was stable at the pH range of 3-11 and remained stable after heating at 100ºC for 20 minutes. The purification results using the chromatographic filtration technique showed that the protein fraction with a molecular weight of 47,38 kDa effectively inhibited V. harveyi growth. Bacillus sp. Lts40 isolate has potential application as a probiotic agent in shrimp ponds to control the growth of V. harveyi that causes luminous vibriosis diseases and the antimicrobial substance is potentially to be developed and produced as an anti-V. harveyi product that can be applied in a shrimp hatchery.
Keywords: Antimicrobial substances; Bacillus; Vibrio harveyi; Shrimp pathogen